Peningkatan pengetahuan lingkungan petani Kecamatan Sabbang Paru Kabupaten Wajo melalui pelatihan pembuatan komposter - Dyah Darma Andayani; Nurlita Pertiwi; Fhatiah Adiba (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This study aims to reveal the description of counseling on organic waste management and its impact on increasing farmers' environmental knowledge. The method in this counseling is done by the method of demonstration and practice. The training participants were 30 farmers in Sabbang Paru District, Wajo District. Data analysis using descriptive methods that present test results with graphs. Based on the results of this counseling, it can be concluded that farmers have been able to understand the technique of making composter with an average value of 76.97 which means it is in the high category. This increase in knowledge was also influenced by the positive response and enthusiasm of the community in participating in this outreach activity.